Kinesiophobia levels in patients with multiple sclerosis: a case-control investigation - Ruiz-Sánchez, Francisco Javier; Martins, Maria do Rosário; Soares, Salete; Romero-Morales, Carlos; López-López, Daniel; Gómez-Salgado, Juan; Jiménez-Cebrián, Ana María (MDPI, 2022)
Fear of movement or kinesiophobia is a health problem related to an irrational fear of physical movement and fatigue that can lead to a limitation of functional capacity and a decrease in daily physical activity. Thus, the purpose of this study was to test the level of kinesiophobia in people with multiple sclerosis and compare it with a group of healthy people. The findings of this research support evidence that kinesiophobia is higher in people with multiple sclerosis than in a healthy control group. Therefore, people with multiple sclerosis should be evaluated and monitored to plan the treatment and preventive care activities of a multidisciplinary health team (podiatrists, physiotherapists, nurses, physicians, occupational therapists) in the attempt to improve their quality of life, autonomy, and wellbeing
Keywords: Esclerosis múltiple - Ejercicios terapéuticos; Ejercicio físico; Calidad de vida; Miedo; Salud de los pies; Kinesiofobia; Movimiento; Esclerosis múltiple